Principles and applications of electrical engineering - Rizzoni, Giorgio; Hartley, T. T. (Tom T.), 1964- (Boston : McGraw-Hill Higher Education, 2007)
Rizzoni provides a solid overview of the electrical engineering discipline that is especially geared toward the many non-electrical engineering students who take this course. The hallmark feature of the text is its liberal use of practical applications to illustrate important principles. (Midwest).
1 Introduction to Electrical Engineering Part I - Circuits 2 - Fundamentals of Electric Circuits 3 - Resistive Network Analysis 4 - AC Network Analysis 5 - Transient Analysis 6 - Frequency Response and System Concepts 7 - AC Power Part II - Electronics 8 - Operational Amplifiers 9 - Semiconductors and Diodes 10 - Bipolar Junction Transistors: Operation, Circuit Models, and Applications 11 - Field-Effect Transistors: Operation, Circuit Models, and Applications 12 - Power Electronics 13 - Digital Logic Circuits 14 - Digital Systems Part III - Instrumentation and Communication Systems 15 - Electronic Instrumentation and Measurements 16 - Analog Communication Systems 17 - Digital Communications Part IV - Electromechanics 18 - Principles of Electromechanics 19 - Introduction to Electric Machines 20 - Special-Purpose Electric Machines Appendices Appendix A - Linear Algebra and Complex Numbers Appendix B - The Laplace Transform Appendix C - Fundamentals of Engineering (FE) Examination Appendix D - Answers to Selected
Includes index.
Keywords: Electrical engineering